Effects of increased variability on motor learning of the short serve in recreational and competitive badminton - Jaitner, T.; Schinz, F. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
In recent years, a growing focus of motor learning research has been put on variability of practise. Based on the coordination dynamics theory variations are no more restricted on movement parameters as proposed by the Schema theory (Schmidt, 1975), but also extended to movement structures. As example, the differencial learning approach tries to utiliize the fluctuations and voluntarily variations in human motor behavior to induce a self-organising process to the athlet which takes advantage of individual movement and learning characteristics. E specially for goal directed movement, increasing the amount of variation to such an extend that no exercise is repeated during the learning process results in superior performance than repeating the same movement many times during acquisition (Frank et al, 2008). The purpose of this study was to investigate effects of differencial learning on the short Badminton serve. Methods: 51 Badminton players of two different levels of expertise (recreational vs. competitive players on regional/national level) participated in a learning experiment with 8 practice sessions. Subjects were divided into a differencial (DT) and a traditional (TT) training group. The TT group started with basic exercises and increased complexity systematically during the experiment. Each exercise was repeated extensively, and feedback was given by demand. For the DT group variations with increasing complexity were implemented in a way that neither exercise was repeated, and no feedback on performance was given. In pretest, posttest and retention test two weeks after the posttest each participant performed 40 serves from two positions on a regular badminton court. All serves must be placed in the service area as closed as possible to the front and centre line. Net clearance and landing position of the shuttle were filmed and than rated on a ten point scale. A performance index was calculated as mean of both scores. Mann-Whitney-U-test was applied to analyze the performance of the subjects that completed all tests. Results and discussion: The recreational as well as the competitive DT group improved performance from pretest to posttest significant, whereas as both TT groups showed no effect. From posttest and retention test the recreational players of the DT as well as of the DT decreased their performance significant. No effect was found for the competitive players. Therefore, a positive learning effect can only be stated for variable practise following the differencial learning approach. Contrary to Frank et al. (2008) a further increase after the acquisition phase can not be observed in this study. Moreover, it can be assumed that only Badminton players on a higher level of expertise are able to maintain their level of performance during the retention phase.